Stanowisko Ludwiga von Misesa wobec historycyzmu i empiryzmu - Szabaciuk, Wojciech (Polityka i Społeczeństwo, 2021)
This article is an attempt to analyze of the standpoint’s one of the most influential representative of Austrian Economics School against historicism and empiricism. This article shows that while Ludwig von Mises shared a standpoint of founder Austrian Economic School Carl Menger’s against historicism, in the area of empirical methods in the social science differences between two key figures of Austrian School existed, and Mises rejected the empirical methods of Menger. The author of this article used an interpretative method of the social science and focused on the text’s analysis. The article will conclude that in the opinion of Mises, historicism is the method of self-contradiction and empirical methods in the social science are imperfect and unreliable in the sphere of prediction future event.